Znaczenie ubezpieczenia należności krajowych dla praktyki gospodarczej - Dankiewicz, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The basic element of market economy is the credit. The credit risk when running a business is generallyimpossible to avoid. The aim of the article is to present the state of knowledge, level of utilizinginsurance insurance receivables in national turnover and tendencies in this field.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 126-130